Household Income Distribution and Hours of Work: An International Comparison - Dominique Anxo; Lennart Flood (Luxembourg Income Study (LIS), 1999)
The aim of this paper is twofold. First, to analyze the relationship between the distribution of household income and the distribution of working time in six European countries and in the United States. The second objective is to assess how the tax and transfer systems affect the gender allocation of working time within married or cohabitant households. This paper is structured in the following manner. Section 2 briefly describes the data set used (Luxembourg Income Study database) and the definition of the population and variables retained in this study. Section 3 describes the main features of income distribution, earnings inequality and household working time patterns in the selected countries. Section 4 tries to assess the impact of national tax and transfer systems on the net earnings return for various household working time patterns. In particular, we provide some preliminary estimates on the marginal effect of an increase of wife's working hours on household's net disposable income.
Keywords: 330; Haushaltseinkommen; Einkommensverteilung; Hausarbeit; Arbeitszeit; Niederlande; Schweden; USA; Belgien; Deutschland; Finnland; Großbritannien